Exploring urban modeling methodologies to better figure out urban gentrification dynamics in developing countries - Soheil, Sabri; Yakkup, Ahris (Faculty of Built Environment, UTM, 2008)
Gentrification has enjoyed the spotlight as a topic of academic inquiry in economics, politics, and sociology for about four decades. The application of urban modeling methodologies for testing ideas and hypotheses relating to urban gentrification dynamics is proved most sophisticated rather the other spatial analysis methods. This article is going to explore the components of urban gentrification in developing countries and find the useful test-bed models to study the phenomenon based of theory-informed scenarios. It is intended to compare the current platforms based on methodologies improved for further work. Ultimately the article will introduce the most reasonable methodology and instruments for modeling and simulating the complex phenomenon of urban gentrification in developing countries’ inner city that was not applied hitherto.